Tissue-specific cytokine release from human extra-placental membranes stimulated by lipopolysaccharide in a two-compartment tissue culture system - Loch-Caruso Rita K; Chames Mark C; Thiex Natalie W (BMC, 2009)
Abstract Background The extra-placental gestational membranes secrete cytokines in response to bacteria and other infectious agents, with potentially adverse consequences for pregnancy. The present study used lipopolysaccharide (LPS) as a prototype endotoxin to investigate the pattern of stimulated cytokine release from the amniotic and choriodecidual sides of full-thickness human gestational membranes in a two-compartment tissue culture system. Methods Gestational membranes were collected from healthy non-laboring caesarean deliveries at term. Full-thickness membranes from each placenta were cut into pieces, mounted on Transwell frames, and placed in culture wells to create a two-compartment culture with the gestational membranes serving as the barrier between compartments. The LPS (100 ng/ml) was added to the amniotic, choriodecidual or both chambers of the culture, and cytokines were assayed in the medium of the amniotic and choriodecidual chambers after 8 h of LPS exposure. Cytokine concentrations were analyzed by two-way analysis of variance for effects of treatment and side specificity of cytokine release from the membranes. Results LPS exposure on the choriodecidual side of the membranes significantly increased TNF-alpha, IL-6, IL-10 and IL-8 in the choriodecidual compartment, whereas TNF-alpha was the only cytokine observed to increase in the amniotic compartment. When LPS treatment was to the amniotic side of the membranes, there were significant increases in TNF-alpha and IL-6 in the amniotic compartment as well as increased concentrations of TNF-alpha, IL-6 and IL-8 in the choriodecidual compartment; however, there were no statistically significant differences for IL-10 in either compartment. No statistically significant differences were observed for IL-1beta, TGF-beta or IL-4 concentrations in response to LPS, regardless of the exposure modality. Conclusion The amnion and choriodecidua exhibited distinct patterns of response to LPS with evidence of inflammatory signaling across the layers of the gestational membranes. These results suggest a complicated network of signaling within the gestational membranes, in which cytokine- and tissue-specific responses to inflammatory stimulation may have important implications for maintaining pregnancy in the challenge of microbial invasion of the uterine compartment.